2020
DOI: 10.1039/c9ce01893j
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of anisotropy effects in the breakup of metallic FCC nanowires into ordered nanodroplet chains

Abstract: We have analyzed the expressed manifestation of the anisotropy of surface energy density in the dynamics of ultrathin nanowires, which break up into disjointed clusters when annealed below their melting temperature. The breakup process is studied for different temperatures and orientations of the nanowire axis relative to its internal crystal structure using the Monte Carlo kinetic method. We have also presented an approximate analytical model of the instability of nanowires. Generally, the interpretation of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 48 publications
5
23
0
Order By: Relevance
“…The first of them was initiated by the results with gold nanowires [32] with a radius of the order of ≈ 7𝑛𝑚. Under the influence of electron beam irradiation, modulations of the radius with the wavelength 𝜆/𝑟 0 ~5.2 − 5.6 appeared in accordance with our estimates of the data given in [48]. We attribute this to the stimulation of the roughening transition in electron bombardment of a nanowire surface.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…The first of them was initiated by the results with gold nanowires [32] with a radius of the order of ≈ 7𝑛𝑚. Under the influence of electron beam irradiation, modulations of the radius with the wavelength 𝜆/𝑟 0 ~5.2 − 5.6 appeared in accordance with our estimates of the data given in [48]. We attribute this to the stimulation of the roughening transition in electron bombardment of a nanowire surface.…”
Section: Introductionsupporting
confidence: 84%
“…In the described model [31], the dynamics of the nanowire is very similar to the results of the classical theory of instability of Plateau-Rayleigh liquid jets [30]. A recent work [48] took into account the possible anisotropy of 𝜎 under the assumption that the shape of a nanowire can also be presented by sinusoidal modulation of its radius along the length. The obtained qualitative results are physically transparent.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Experimentally, it is known that single-crystalline and poly-crystalline metallic nanowires possess faceted morphologies and this preference in surface orientation is attributed to surface energy anisotropy [21]. The diverse effects of surface energy anisotropy in FCC metallic nanowires have been investigated using Monte Carlo models [18]. It has been reported that Au nanowires develop facets as a result surface diffusion in order to minimize the surface energy [30].…”
Section: Effect Of Interfacial Energy Anisotropymentioning
confidence: 99%
“…The effect of nanowire size, network density and temperature on the stability of metallic nanowires have been investigated experimentally [8,9,10]. The structural stability of the metallic nanowires at the nanoscale is governed by numerous factors -the most dominant factors being Rayleigh instability [11,12,13] and anisotropy in interfacial energy [14,15,16,17,18]. Thermally accelerated surface diffusion plays a central role in the resulting change in morphology of the metallic nanowires due to Rayleigh instability, and their subsequent break-up into nanodots [19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%